XPS study of triangular GaN nano/micro-needles grown by MOCVD technique - Kumar, Mukesh; Kumar, Ashish; Thapa, S. B.; Christiansen, Silke; Singh, R. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2014)
Triangular GaN nano/micro scale needles (TGN) grown on nickel coated c-plane sapphire substrate with highly dense ensemble of TGN and low dense ensemble of TGN have been investigated in the present work. The observed morphology of these TGN is in the form of triangular faceted needle like structures with average length in the order of fifty micrometres and cross-sections range from 500 nm to 3 μm near the base of TGN. X-ray diffraction spectra illustrate the wurtzite crystal structure of TGN and better crystalline nature of the highly dense ensemble of TGN. Analysis of the X-ray photoelectron spectroscopy core level spectra shows that surfaces with highly dense ensemble of TGN and low dense ensemble of TGN interact differently with the unintended impurities (such as oxygen and carbon) and these impurities exhibit low reactivity (chemical modifications) to the surface of highly dense ensemble of TGN. © 2014 Elsevier B.V.
CRIS-Team Scopus Importer:2023-03-07
Keywords: GaN; MOCVD; Nano/micro-needles; XPS